2016
DOI: 10.1073/pnas.1520371113
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus features coded by single neurons of a macaque body category selective patch

Abstract: Body category-selective regions of the primate temporal cortex respond to images of bodies, but it is unclear which fragments of such images drive single neurons' responses in these regions. Here we applied the Bubbles technique to the responses of single macaque middle superior temporal sulcus (midSTS) body patch neurons to reveal the image fragments the neurons respond to. We found that local image fragments such as extremities (limbs), curved boundaries, and parts of the torso drove the large majority of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…Analogous to classical hierarchical feature models of visual object recognition (Tanaka 1997), a viable hypothesis is that the brain processes whole-body movements by coding a range of movement features at different levels of complexity and ultimately arrives at a coherent percept through feature integration. As an example in line with this, recent monkey studies found that information in the mid-superior temporal sulcus (STS) related to body category perception is organized in the brain not so much by semantic categories than by feature statistics of the body (Popivanov et al 2016). Yet, there is currently no example of a hierarchical computational model-based approach to visual processes involved in movement perception in humans.…”
Section: Introductionmentioning
confidence: 75%
“…Analogous to classical hierarchical feature models of visual object recognition (Tanaka 1997), a viable hypothesis is that the brain processes whole-body movements by coding a range of movement features at different levels of complexity and ultimately arrives at a coherent percept through feature integration. As an example in line with this, recent monkey studies found that information in the mid-superior temporal sulcus (STS) related to body category perception is organized in the brain not so much by semantic categories than by feature statistics of the body (Popivanov et al 2016). Yet, there is currently no example of a hierarchical computational model-based approach to visual processes involved in movement perception in humans.…”
Section: Introductionmentioning
confidence: 75%
“…As such, our approach adds to a growing body of studies combining classification images with other computational methods to predict perceptual decisions [ 30 , 41 , 42 , 43 ] and infer visual processing mechanisms from behavioral and neurophysiological data [ 37 , 43 , 44 , 45 , 46 ]. Future behavioral studies could take inspiration from these approaches to investigate aspects of rodent vision that were beyond the scope of our experiments—e.g., the representation of object information in different spatial frequency bands could be explored, by relying on multi-resolution generative or filtering manipulations [ 34 , 44 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Popivanov et al (2016) showed that single MSB neurons are sensitive to removal of some parts of an effective shape. Thus, this part manipulation provides an additional set of stimuli to which we measured responses and that could be used as an independent test of the shape selectivity models.…”
Section: Methodsmentioning
confidence: 99%